Membangun Generasi Qur’ani:Strategi Manajerial dalam Pendidikan Bahasa Arab di Lembaga Islam - Hamdy, Mohammad Zainal; Mabrurrosi, Mabrurrosi (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2026)
This study aims to analyze managerial strategies in building a Qur’anic generation through Arabic language education at Madrasah Miftahul Ulum Angsokah Timur. The research focuses on how such strategies are designed, implemented, and evaluated within the context of Islamic educational institutions. This is a qualitative study using a case study method. Data were collected through participatory observation, in-depth interviews, and documentation, with key informants including the head of the madrasah, teachers, students, and institutional documents. The findings reveal that the managerial strategies in practice are still traditional, undocumented, and heavily dependent on teachers’ loyalty and the strength of pesantren-based cultural values. A surprising finding is that teachers’ sincerity and dedication have become the main driving forces behind the institution, replacing the role of a formal management system that has yet to be optimized. This research contributes a new perspective: Islamic educational management based on Qur’anic values is not solely determined by formal structure but is also shaped by the strength of social and spiritual community relationships. The study concludes that integrating Qur’anic values with professional governance is essential for sustaining community-based Islamic education